2011
DOI: 10.1515/bc.2011.058
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of the dpm2 and dpm3 genes from Trichoderma reesei expressed in a Saccharomyces cerevisiae dpm1Δ mutant strain

Abstract: In Trichoderma reesei, dolichyl phosphate mannose (dpm) synthase, a key enzyme in the O-glycosylation process, requires three proteins for full activity. In this study, the dpm2 and dpm3 genes coding for the DPMII and DPMIII subunits of T. reesei DPM synthase were cloned and functionally analyzed after expression in the Saccharomyces cerevisiae dpm1Δ [genotype (BY4743; his3Δ1; /leu2Δ0; lys2Δ0; /ura3Δ0; YPR183w::kanMX4] mutant. It was found that apart from the catalytic subunit DPMI, the DPMIII subunit is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 45 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, a chimeric T. reesei DPMI protein with the yeast transmembrane domain at the C terminus was also not functional in a yeast dpm1⌬ mutant (581). Expression of different combinations of the dpm1, dpm2, and dpm3 genes from Trichoderma in yeast revealed that besides the DPMI catalytic subunit, DPMIII subunit is indispensable for rescuing the dpm1⌬ mutation (582). In contrast, the Dpm1 protein from S. cerevisiae itself is functional in Trichoderma.…”
Section: Glycosylationmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, a chimeric T. reesei DPMI protein with the yeast transmembrane domain at the C terminus was also not functional in a yeast dpm1⌬ mutant (581). Expression of different combinations of the dpm1, dpm2, and dpm3 genes from Trichoderma in yeast revealed that besides the DPMI catalytic subunit, DPMIII subunit is indispensable for rescuing the dpm1⌬ mutation (582). In contrast, the Dpm1 protein from S. cerevisiae itself is functional in Trichoderma.…”
Section: Glycosylationmentioning
confidence: 97%
“…In Trichoderma, DPM synthase forms an enzymatic complex of three proteins, DPMI, DPMII, and DPMIII (581,582), which contrasts with the situation in yeast, where DPM synthase consists of a single Dpm1 protein (583,584). The yeast Dpm1 protein is an equivalent of the DPMI catalytic subunit of Trichoderma DPM synthase (582).…”
Section: Glycosylationmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, we prove that the expression of CaDPM1 alone was not sufficient to rescue the lethal deletion of S. cerevisiae DPM1 (Fig. 2), similar to human and S. pombe DPM1 [12] or T. reseei dpm1 [14]. When expressed in S. cerevisiae CaDPM1 together with CaDPM3 were essential for the formation of functional DPMS complex which suppressed ScΔdpm1 phenotype, whereas additional presence of CaDpm2 increased the enzymatic activity and improved cell fitness.…”
Section: Discussionmentioning
confidence: 65%
“…The enzymes belonging to the second class are composed of three subunits. To this class belong human [11], Schizosaccharomyces pombe [12], Trichoderma reesei [13,14] or Arabidopsis thaliana DPMS [15]. The group of T. Kinoshita in a series of papers described functions and interactions of three subunits of human DPMS.…”
Section: Introductionmentioning
confidence: 99%